Sequential Analysis of Trace Elements in a Micro Volume Urine Sample Using Inductively Coupled Plasma Mass Spectrometry - Nico Laur; Lars Kaiser; Hans-Peter Deigner; Ralf Kinscherf (Applied Sciences, 2021)
In this work, we describe a simple, fast, cheap, accurate and high-throughput method for the determination of Al; V; Cr; Mn; Fe; Co; Cu; Zn; As; Se; Mo; Cd; Sn; Ba; TI; Pb in a micro volume of urine by using inductively coupled mass spectrometry (ICP-MS) equipped with an octupole-based collision cell. The samples were directly analyzed after a simple acidification with 3% nitric acid. Validation of this method was performed by using certified urine reference material. He and H were used as collision gas for reducing polyatomic interference for most of the measured elements. Finally, we partook in an external quality assurance conducted by ISNTAND e.V. 2. Results show that our high-throughput method is ideal for detecting elements in newborns and infants because of its simplicity, speed, accuracy and low sample volume.